Sleep Characteristics of Highly Trained Wheelchair Rugby Athletes With and Without a Cervical Spinal Cord Injury During the Competitive Season - Conor J. Murphy; Conor J. Murphy; Iuliana Hartescu; Ifan E. Roberts; Christof A. Leicht; Christof A. Leicht; Vicky L. Goosey-Tolfrey; Vicky L. Goosey-Tolfrey (Frontiers Media S.A., 2021)
Sleep behaviors although significantly relevant to exercise recovery are poorly characterized in Para-sport athletes. Therefore, the main aims of this study were to describe sleep quality and quantity of highly trained wheelchair rugby (WR) athletes during the competitive season, and to investigate whether impairment type or attending a training camp influenced sleep outcomes. Eighteen male WR athletes (mean ± SD; age: 30 ± 5 years) with cervical spinal cord injuries (n = 11) (CSCI) and without (n = 7) (NON-SCI) wore an activity monitor over a 16-day period to objectively quantify sleep parameters, while the Pittsburgh Sleep Quality Index (PSQI) and nightly sleep diary entries were used as subjective means. A sub-sample of the athletes (n = 11) had their sleep monitored during a 3-night training camp to assess the impact of environmental change on sleep. Furthermore, as an additional exploratory measure core temperature was measured for a single night-time period using ingestible telemetry capsules. The athletes had total sleep times and sleep efficiency scores of 7.06 (1.30) h.min [median (interquartile range)] and 81 (9)%, respectively. Sleep onset latency and wake after sleep onset were 13 (24) min and 1.11 (0.45) h.min, respectively. No significant differences were found in objective sleep variables between the impairment groups despite the CSCI group being significantly more likely to report a poorer night's sleep (p = 0.04). Furthermore, attending the training camp caused a significant reduction in total sleep time for both groups [Δ38 ± 33 min; (95% CI: 18-60 min) p < 0.01]. This study highlights suboptimal sleep characteristics that are present in both CSCI and NON-SCI wheelchair athletes, as defined by the National Sleep Foundation. Although objective scores did not differ between groups, athletes with a CSCI rated their sleep worse. Furthermore, the disruption of sleep during training camp reflects an additional risk factor that is important to recognize for those working with wheelchair athletes.